Economic complexity, structural transformation and economic growth in a regional context: Evidence for Brazil - Orsolin Teixeira, Felipe; José Missio, Fabricio; Dathein, Ricardo (PSL Quarterly Review, 2022)
The purpose of this paper is to verify the effect of economic complexity on the growth and productive transformation of federative units (UFs) in Brazil between 2003 and 2014. We also analyze the factors that determine the economic complexity of these subnational entities. To do this we used different indices of economic complexity (linear and non- linear), as well as system generalized method of moments (GMM-SYS) estimators in dynamic panels to avoid endogeneity problems. The results showed that: i) through the descriptive analysis (both by the linear and the non- linear versions) a positive relationship between the UFs’ economic complexity and economic growth was observed; ii) the econometric analysis showed that measures of economic complexity are positively related to economic growth – however, some of the coefficients did not show statistical significance and the coefficients that represent the non- linear approach showed weak correlation; iii) there is a positive relationship between the real exchange rate at the state level (R/US) and the UFs’ productive transformation, such as between the UFs’ productive transformation and the economic complexity.